Clinical impact of primary tumor sidedness and sex on unresectable post-recurrence survival in resected pathological stage II-III colorectal cancers: a nationwide multicenter retrospective study - Abe, Shinya; Kawai, Kazushige; Nozawa, Hiroaki; Sasaki, Kazuhito; Murono, Koji; Emoto, Shigenobu; Ozawa, Tsuyoshi; Yokoyama, Yuichiro; Nagai, Yuzo; Anzai, Hiroyuki; Sonoda, Hirofumi; Yamauchi, Shinichi; et al. (BMC Cancer, 2022)
Several studies have demonstrated that right-sided tumors have poorer prognosis than left-sided tumors in patients with unresectable colorectal cancer (CRC). The predictive ability of the tumor sidedness in CRC treated with chemotherapy in each sex is unclear. Subjects were 964 unresectable recurrent patients treated with chemotherapy with stage II-III CRC after curative resection between 2004 and 2012. Post-recurrence cancer-specific survival (CSS) for each sex was examined. Patients were 603 males (222 right-side tumors (cecum to transverse colon) and 381 left-sided tumors (descending colon to rectum)), and 361 females (167 right-side tumors and 194 left-sided tumors). Right-sided tumors developed peritoneal recurrences in males and females. Left-sided tumors were associated with locoregional recurrences in males and with lung recurrences in females. Right-sided tumors were associated with shorter post-recurrence CSS in both sexes. In males, multivariate analyses showed that right-sided tumors were associated with shorter post-recurrence CSS (HR: 1.53, P < 0.0001) together with the presence of regional lymph node metastasis histopathological type of other than differentiated adenocarcinoma, the recurrence of liver only, the recurrence of peritoneal dissemination only, and relapse-free interval less than one-year. In females, multivariate analyses showed that right-sided tumors were associated with shorter post-recurrence CSS (HR: 1.50, P = 0.0019) together with advanced depth of invasion, the presence of regional lymph node metastasis, and recurrence of liver only. Primary tumor sidedness in both sexes in unresectable recurrent CRC patients treated with chemotherapy may have prognostic implications for post-recurrence CSS.